Dynamic reservoir-condition microtomography of reactive transport in complex carbonates: effect of initial pore structure and initial brine pH - Menke,HP; Bijeljic,B; Blunt,M (Geochimica et Cosmochimica Acta, 2017)
We study the impact of brine acidity and initial pore structure on the dynamics of fluid/solid reaction at high Péclet numbers and low Damköhler numbers. A laboratory μ-CT scanner was used to image the dissolution of Ketton, Estaillades, and Portland limestones in the presence of CO2-acidified brine at reservoir conditions (10 MPa and 50°C) at two injected acid strengths for a period of 4 hours. Each sample was scanned between 6 and 10 times at ∼4 μm resolution and multiple effluent samples were extracted. The images were used as inputs into flow simulations, and analysed for dynamic changes in porosity, permeability, and reaction rate. Additionally, the effluent samples were used to verify the image-measured porosity changes.We find that initial brine acidity and pore structure determine the type of dissolution. Dissolution is either uniform where the porosity increases evenly both spatially and temporally, or occurs as channelling where the porosity increase is concentrated in preferential flow paths. Ketton, which has a relatively homogeneous pore structure, dissolved uniformly at pH = 3.6 but showed more channelized flow at pH = 3.1. In Estaillades and Portland, increasingly complex carbonates, channelized flow was observed at both acidities with the channel forming faster at lower pH. It was found that the effluent pH, which is higher than that injected, is a reasonably good indicator of effective reaction rate during uniform dissolution, but a poor indicator during channelling. The overall effective reaction rate was up to 18 times lower than the batch reaction rate measured on a flat surface at the effluent pH, with the lowest reaction rates in the samples with the most channelized flow, confirming that transport limitations are the dominant mechanism in determining reaction dynamics at the fluid/solid boundary.